Implementasi Metode Hafalan dalam Pembelajaran Ilmu Al-Qur’an di Pondok Pesantren Tahfidz At-Taqwa Tritunggal Babat Lamongan - Muchammad Ali Zubaedi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The teaching of Qur’anic studies constitutes the core of education in Islamic boarding schools, particularly at Tahfidz At-Taqwa Islamic Boarding School in Tritunggal, Babat, Lamongan, which has a special focus on Qur’an memorization (tahfidz). One of the classical methods that continues to be applied is the memorization method (tahfidz). This study aims to describe the implementation of the memorization method in teaching Qur’anic studies at Tahfidz At-Taqwa Islamic Boarding School and to analyze its strengths and challenges in enhancing students’ understanding. This research employs a qualitative approach with a field research design. Data collection techniques include observation, interviews, and documentation. The findings reveal that the memorization method is implemented systematically through stages of memorization submission, muraja’ah (revision), and periodic evaluation. This method is effective in fostering discipline and perseverance and strengthening students’ memory of Qur’anic verses; however, it also faces challenges such as learning fatigue and differences in students’ abilities, given that the students come from diverse backgrounds and age groups. This study recommends integrating the memorization method with meaning-based comprehension approaches to improve the quality of Qur’anic studies instruction in Islamic boarding schools.   Keywords: Memorization Method, Qur’an Studies, Islamic Boarding Schools, Tahfidz